Comparison of Paper Waste Hydrolysis Using Potassium Hydroxide From Empty Palm Fruit Bunch Ash and Commercial Potassium Hydroxide - Panjaitan, Jabosar Ronggur Hamonangan; Riziq, Annisa Zahara; Fadhila, Syalsa; Sanjaya, Andri; Alhanif, Misbahudin (Journal of Chemical Process Engineering, 2024)
Paper waste is one type of waste that is quite abundant. Effective processing of paper waste can be done using hydrolysis process because this process can decompose lignocellulose compounds in paper waste into simpler compound such as glucose and other derivative products. Hydrolysis process was generally carried out using chemical catalysts such as acids, bases and enzymes. In this study, paper waste hydrolysis was investigated using base catalysts such as potassium hydroxide (KOH) from palm oil empty fruit bunches (POEFB) ash and commercial KOH. The research stages began with the preparation of POEFB ash, KOH production from POEFB ash, paper waste preparation, and the hydrolysis process of paper waste using KOH from POEFB ash and commercial KOH. This study uses variations in hydrolysis time were carried out to evaluate the hydrolysis conversion. Based on the research, it was showed that KOH catalyst from POEFB ash contain potassium compounds in the form of 5.87% potassium oxide (K2O) and 31.45% potassium carbonate (K2CO3). Comparison of catalyst performance between KOH catalyst from POEFB ash and commercial KOH catalyst showed that commercial KOH catalyst was better than KOH catalyst from POEFB ash. The effect of hydrolysis reaction time was directly proportional to the conversion value that the highest conversion was 12.11% at 90 minutes using commercial KOH catalyst.